RETRACTED: Power and Gender Oppression in Lauren Weisberger’s The Devil Wears Prada and Seth Graham Smith’s Pride and Prejudice and Zombies - Erliska, Erliska (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2017)
Following a rigorous, carefully concerns and considered review of the article published in Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya to article entitled “POWER AND GENDER OPPRESSION IN LAUREN WEISBERGER’S THE DEVIL WEARS PRADA AND SETH GRAHAM SMITH’S PRIDE AND PREJUDICE AND ZOMBIES” Vol 45, No 2 (Agustus 2017) URL: https://journal2.um.ac.id/index.php/jbs/article/view/1727 This paper has been found to be in violation of the Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya’ publication principles and has been retracted. The article contained redundant material, the editor investigated and found that the paper published in International Conference on Education and Science 2017 (ICONS 2017) Proceeding ISBN: 978-602-61512-1-6, URL: https://icons.upy.ac.id/2017/11/15/power-and-gender-oppression-in-lauren-weisbergers-the-devil-wears-prada-and-seth-graham-smiths-pride-and-prejudice-and-zombies The document and its content has been removed from Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajaranny, and reasonable effort should be made to remove all references to this article.